2022
DOI: 10.1186/s12889-022-14567-x
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 mortality rate determinants in selected Eastern European countries

Abstract: Background The COVID-19 pandemic has caused increased mortality worldwide. We noticed a tendency for higher number of deaths in Eastern European countries. Therefore, we decided to investigate whether any common factor that might be responsible for the increased COVID-19 mortality exists. Methods In our cross-sectional study, we conducted the correlation and multiple regression analysis using R basing on the data gathered in publicly available data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 28 publications
0
7
0
1
Order By: Relevance
“…Possible factors influencing the observed higher proportion of COVID-19-related deaths in upadacitinib-treated patients with PsA include higher mean age compared to those in the AS and nr-axSpA cohorts as well as higher rates of metabolic syndrome, non-biologic DMARD use, and CV risk factors. Other potential contributing factors include low rates of COVID-19 vaccination, geographical predominance in Eastern Europe where increased COVID-19 mortality was reported [ 25 ], and a potential protective effect of TNF inhibitor treatment for adverse COVID-19 outcomes [ 26 ]. Ultimately, the crucial role of COVID-19 vaccination in reducing risks should be underlined, and effective vaccination strategies are possible for patients receiving JAKi therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Possible factors influencing the observed higher proportion of COVID-19-related deaths in upadacitinib-treated patients with PsA include higher mean age compared to those in the AS and nr-axSpA cohorts as well as higher rates of metabolic syndrome, non-biologic DMARD use, and CV risk factors. Other potential contributing factors include low rates of COVID-19 vaccination, geographical predominance in Eastern Europe where increased COVID-19 mortality was reported [ 25 ], and a potential protective effect of TNF inhibitor treatment for adverse COVID-19 outcomes [ 26 ]. Ultimately, the crucial role of COVID-19 vaccination in reducing risks should be underlined, and effective vaccination strategies are possible for patients receiving JAKi therapy [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the pandemic progressed, their perspective on these experiences evolved. An in-depth analysis by Cho and Kim ( 38 ) aiming at categorizing and characterizing the psychological reactions of nurses, who experienced the care of a patient with COVID-19, was based on a methodology which showed that psychological reactions can be divided into three areas: ( 1 ) fear of social stigma, ( 2 ) anxiety related to the risk of infection and ( 3 ) the burden of infection prevention and nursing control. In our findings, all of these areas were reported by nurses through their experience of caring for older patients in the PHC.…”
Section: Discussionmentioning
confidence: 99%
“…When the COVID-19 pandemic was compared across Europe in terms of numbers of deaths, crude rates, and adjusted mortality trend ratios (AMTRs), it was found that Eastern European countries (Hungary, the Czech Republic, Slovakia, and Poland) had higher AMTRs than Western European countries ( 1 ). This outcome is related to social, economic, and healthcare quality factors ( 2 ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to this, the ill-prepared health system in Bulgaria also contributed to the extraordinarily high mortality rates, as according to data published by Eurostat, Central/Eastern European countries tend to spend less as a percentage of their budgets on healthcare compared to Western countries [ 28 ]. It has been suggested that the higher COVID-19 mortality rates in CEE countries compared to Western Europe may also be due to the overall quality of healthcare [ 29 ]. The vulnerability of Eastern European countries in terms of healthcare infrastructure, medical staff, and consistent decision-making puts them at risk in an epidemic [ 28 ].…”
Section: Discussionmentioning
confidence: 99%